2012
DOI: 10.1088/1367-2630/14/1/013051
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear spectroscopy of superconducting anharmonic resonators

Abstract: We formulate a model for the steady state response of a nonlinear quantum oscillator structure, such as those used in a variety of superconducting qubit experiments, when excited by a steady, but not necessarily small, ac tone. We show that this model can be derived directly from a circuit description of some recent qubit experiments in which the state of the qubit is read out directly, without a SQUID magnetometer. The excitation profile has a rich structure depending on the detuning of the tone from the smal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…This is the Hamiltonian operator of the quantum Duffing model. The Duffing model has received a considerable attention in the recent literature [51][52][53][54][55][56] especially in the context of superconducting transmon realizations. It is worthwhile to notice that in this regime the potential is no longer periodic and, thus, we can neglect the periodic boundary condition of the wavefunction.…”
Section: Low-energy Limit: Duffing Oscillatormentioning
confidence: 99%
“…This is the Hamiltonian operator of the quantum Duffing model. The Duffing model has received a considerable attention in the recent literature [51][52][53][54][55][56] especially in the context of superconducting transmon realizations. It is worthwhile to notice that in this regime the potential is no longer periodic and, thus, we can neglect the periodic boundary condition of the wavefunction.…”
Section: Low-energy Limit: Duffing Oscillatormentioning
confidence: 99%
“…In fact, quantum nonlinear oscillators (NLO) have been implemented in several settings, including trapped ions (where the trapping potential can be modified to include nonlinearities [19]), optomechanical systems (where tunable nonlinearities have been realized [20]), and atoms in optical lattices [21]. Interestingly, it has been shown that the inclusion of strong enough nonlinearities in the oscillator potential allows new possibilities to generate non-classical states [22][23][24][25][26][27]. However, despite the promising experimental progresses in the control and fabrication of NLO, it is still a challenge to achieve significant nonlinearities (for a more detailed * Electronic address: v.montenegro.11@ucl.ac.uk † Electronic address: a.ferraro@qub.ac.uk ‡ Electronic address: sougato@theory.phys.ucl.ac.uk discussion about the nonlinear regimes and their possible experimental implementations see Sec.…”
Section: Introductionmentioning
confidence: 99%
“…Such quantum decoherence can often cause severe distortion to a quantum state rendering many quantum systems in the real world useless [3][4][5][6][7][8][9][10]. In order to protect a quantum state, many methods against decoherence have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between a quantum system and its environment inevitably leads to the decoherence [1,2] of a quantum state. Such quantum decoherence can often cause severe distortion to a quantum state rendering many quantum systems in the real world useless [3][4][5][6][7][8][9][10]. In order to protect a quantum state, many methods against decoherence have been studied.…”
Section: Introductionmentioning
confidence: 99%